Characterization and genomic analysis of Bacillus megaterium with the ability to degrade aflatoxin B1 - Li, Ting; Chang, Xiaoxi; Qiao, Zixuan; Ren, Guangxi; Zhou, Na; Chen, Jiaxin; Jiang, Dan; Liu, Chunsheng (Frontiers in Microbiology, 2024)
Coix seed is a good product for both medicinal and food use, which is highly susceptible to Aflatoxin B1(AFB1) contamination during field transport, storage and processing. The aim of this study is to find microbial strains that can solve the problem of contamination of Coix seed. In this study, the AFB1degrading microorganism SX1-1 was isolated and identified as a Bacillus megaterium based on morphology, microscopy and 16S rDNA sequencing. The optimum culture conditions for SX1-1 to degrade AFB1 were determined to be 12 h. The optimum degradation conditions were 72 h, 57°C and an initial pH of 8.0. The active component of this strain was the fermentation supernatant, which was able to degrade 97.45% of AFB1 in liquid medium. In addition, whole-genome sequencing analysis of this strain revealed the presence of a number of enzymes that could potentially degrade AFB1. Importantly, SX1-1 was able to degrade AFB1contaminated Coix seeds in situ by 50.06% after co-culture. In conclusion, this strain had a high AFB1 degradation ability, and has great potential and great application as a biocontrol agent for AFB1 degradation of Coix seed.